ANALISIS MODAL SOSIAL DALAM PENGELOLAAN MATA AIR DI DUSUN NGARAM-ARAM, DESA CREWEK, KECAMATAN KRADENAN, KABUPATEN GROBOGAN (Analysis of social capital in springs management at Ngaram-aram Hamlet, Crewek Village, Kradenan District, Grobogan Regency) - Baharinawati Wilhan Hastanti; Purwanto Purwanto (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTSGrobogan Regency is one of the areas in Central Java that experiences drought almost every year. However, Ngaram-aram Hamlet in Crewek Village in the Grobogan Regency almost has not affected by drought in the dry season due to some springs located in this area. Increasing the community participation in water management could be obtained by strengthening the social capital. The objective of this study is to determine the social capital variables in the management of springs by identifying: 1) trust and community solidarity in spring’s management, 2) social Norms in spring’s management, and 3) social networks in spring’s management. The results of the research show that spring’s management was carried out both physically and spiritually. Trust and solidarity in spring’s management could be seen in regulating and distributing water to houses, and in contributing to the finance of spring’s management. The existing social norm is in the form of command sand prohibitions in spring’s management that contain social values, rewards and punishments. The social network in spring’s management at Ngaram-aram appears in a special set of relationships among groups of people who utilize the springs with characteristics of relationships that could be used to interpret social behavior motives from the people involved in them. This network has economic function to obtain water for household and agricultural purposes, social function in security and socialization, and communication flow of information. Indicators of the social network existence could be seen from 1) individual centrality 2) individual closeness, and 3) togetherness between individuals.Keywords: social capital; springs; management ABSTRAKKabupaten Grobogan adalah salah satu wilayah di Jawa Tengah yang hampir setiap tahun mengalami kekeringan. Namun demikian, Dusun Ngaram-aram di Desa Crewek yang termasuk dalam wilayah Kabupaten Grobogan hampir tidak terdampak kekeringan di musim kemarau karena adanya mata air yang bersumber di kawasan tersebut. Peningkatan partisipasi masyarakat dalam pengelolaan air dapat diperoleh melalui penguatan modal sosial. Penelitian ini bertujuan mengetahui variabel-variabel modal sosial dalam pengelolaan mata air dengan mengidentifikasi: 1) kepercayaan dan solidaritas masyarakat dalam pengelolaan mata air, 2) norma sosial dalam pengelolaan mata air, dan 3) jaringan sosial dalam pengelolaan mata air. Hasil penelitian menunjukkan pengelolaan mata air dilakukan secara fisik dan spiritual. Bentuk-bentuk kepercayaan dan solidaritas dalam pengelolaan mata air berupa kepercayaan dan solidaritas dalam mengatur distribusi air ke rumah-rumah, urunan dalam pembiayaan yang terkait dengan pengelolaan mata air. Norma sosial yang ada berupa perintah dan larangan dalam pengelolaan mata air yang mengandung nilai-nilai sosial, penghargaan, dan hukuman. Jaringan sosial dalam pengelolaan mata air di Ngaramaram tampak pada seperangkat hubungan khusus di antara sekelompok warga yang memanfaatkan mata air, dengan karakteristik hubungan yang dapat digunakan untuk menginterpretasikan motif perilaku sosial dari orang-orang yang terlibat di dalamnya. Jaringan tersebut berfungsi ekonomi dalam memperoleh air untuk kebutuhan rumah tangga dan pertanian, jaminan sosial dan sosialisasi, dan komunikasi. Indikator-indikator keberadaan jaringan sosial dilihat dari 1) sentralitas individu, 2) kedekatan individu, dan 3) kebersamaan antar individu.Kata kunci: modal sosial; pengelolaan; mata air